Pertumbuhan dan Hasil Dua Varietas Kangkung Darat pada Media yang Diberi Limbah Cair Kilang Minyak PT Pertamina UP VI Balongan - A.H. Syaeful Anwar (Fakultas Pertanian, Universitas Syiah Kuala, 2010)
Growth and Yield of Two Varieties Kale in Poured Media by Lagoon Liquid Waste PT Pertamina UP VI BalonganABSTRACT. Farmers around of PT Pertamina UP VI Balongan in part cultivated kale because it easily cultivated and short harvest age, however they faces difficulty to find irrigation water in dry season. Therefore it is needed to conduct a research for studying whether liquid waste in the lagoon can be used for plant cultivation. The research was conducted from February 2007 until July 2007 in plastic house in area of PT Pertamina UP VI Balongan on altitude 3 metres above sea level. Experiment design used was Randomized Completely Block Design (RCBD). Experimented factors were two varieties kale: Amanda, Bangkok LP 1 and eight kinds of media: rice field poured by lagoon liquid waste 9, rice field poured by lagoon liquid waste 18, sediment poured by irrigation water, sediment poured by lagoon liquid waste 1, sediment poured by lagoon liquid waste 9, and sediment poured by lagoon liquid waste 18. There were 16 treatment combinations with 3 replications. Observed variable comprised of plant height, total of leaves, total of branches, leaves wide, longest root length, stem fresh weight, root fresh weight, plant fresh weight, stem dry weight, root dry weight, and plant dry weight. This research showed that poured media by liquid waste in lagoon do not decrease growth and yield of kale, except in longest root length. Variety of Bangkok LP 1 have longest root length of 33.48 cm while variety of Amanda of 30.55 cm.